2014
DOI: 10.1155/2014/354264
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Medicinal Foods

Abstract: Pharmaceutical and nutritional sciences have recently witnessed a bloom in the scientific literature geared towards the use of food plants for their diversified health benefits and potential clinical applications. Health professionals now recognize that a synergism of drug therapy and nutrition might confer optimum outcomes in the fight against diseases. The prophylactic benefits of food plants are being investigated for potential use as novel medicinal remedies due to the presence of pharmacologically active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 132 publications
2
41
0
1
Order By: Relevance
“…In this context, Çam, Içyer & Erdogna, (2014) tested the incorporation of microencapsulated Punica granatum L., an extract from pomegranate, in ice creams, and Martins et al, (2014) studied the incorporation of Rubus ulmifolius Schoot (Rosaceae), a species of wild blackberry, microencapsulated in alginate microparticles, in a dairy product, yogurt. The obtained results, rather preliminary, are motivating corroborating the interest of developing foods enriched with natural extracts that are often referred as health promoters (Ramalingum & Mahomoodally, 2014).…”
Section: Introductionsupporting
confidence: 57%
“…In this context, Çam, Içyer & Erdogna, (2014) tested the incorporation of microencapsulated Punica granatum L., an extract from pomegranate, in ice creams, and Martins et al, (2014) studied the incorporation of Rubus ulmifolius Schoot (Rosaceae), a species of wild blackberry, microencapsulated in alginate microparticles, in a dairy product, yogurt. The obtained results, rather preliminary, are motivating corroborating the interest of developing foods enriched with natural extracts that are often referred as health promoters (Ramalingum & Mahomoodally, 2014).…”
Section: Introductionsupporting
confidence: 57%
“…Medicinal food plants, including artichokes, are in widespread use-and sometimes have been in use for centuries (40)(41)(42)(43)(44). Their medical benefit is often anecdotal and does not always hold up to strict scientific criteria (45).…”
Section: Discussionmentioning
confidence: 99%
“…Fishes are only a source of animal protein required by human but they are been widely used in combatting certain disease condition including would healing. Typically, Ramalingum and Mahomoodally (2014) reported that pharmaceutical and nutritional sciences appear to be coexisting for maintaining normal human health. This is because several food resources are being used in treatment of several types of diseases.…”
Section: Fishes and Their Roles In Human Healthmentioning
confidence: 99%